CONCEPTION OF THE ARDUINO PLATFORM AS A BASE FOR THE CONSTRUCTION OF DISTRIBUTED DIAGNOSTIC SYSTEMS - Tomasz HANISZEWSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
Systems for distributed parameter measurements are very expensive solutions; however, they offer many possibilities in terms of real-time verification of machine status. Of course, ready, complex and easy-to-use measuring systems can be used, where the cost of such a solution may be prohibitive. In the case of research carried out under the experimental sphere of an object, e.g., using a research measurement system, it is possible to create a project for a system based mainly on the Arduino platform. As an example, the concept of a distributed measurement system will be presented, with the possibility for use on cranes and conveyors, i.e., on the most common machines on industrial plants.